ENHANCING THE FIRST SEMESTER STUDENTS’ SPEAKING ABILITY USING INSTRUCTIONAL VIDEO - Sri Fatmaning Hartatik; Ike Dian Puspitasari (Journey: Journal of English Language and Pedagogy, 2018)
This one-cycle Clasroom Action Research (CAR) was intended to improve students’ speaking abilty indescribing someone. This was done because the researchers’ observation during preliminary studyshowed that students found difficulties in delivering their thought in speaking. It was indicated by theirhesitation to present their thoughts. Besides, from some students’ performance during preliminary study,the researchers found that students still found difficuties to pronounce English words. To this,instructional video implementation was selected to eliminate this problem. After the plannings wereimplemented, the results of video implementation was reflected by reflecting the revealed scores with thecriteria of success. Finally, it was found that using instructional video in teaching speaking did not onlyimprove students’ speaking ability but also motivate students to participate actively in the teaching andlearning process.